Urinary complement profile in IgA nephropathy and its correlation with the clinical and pathological characteristics - Wang, Dongqing; Wu, Changwei; Chen, Sipei; Li, Yi; Wang, Li; Zhang, Yong; Li, Guisen (Frontiers in Immunology, 2023)
Background and objectives The activated complement profile in IgA nephropathy (IgAN) is still unclear. Our study investigated the profile of urinary complements in IgAN patients and its correlations with clinical and pathological characteristics. Methods Urinary protein abundance was detected by liquid chromatography-tandem mass spectrometry (LC‒MS/MS) in 50 IgAN, 50 membranous nephropathy (MN), and 68 healthy controls (HC). Then, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed to identify differentially expressed proteins in IgAN patients. The differentially expressed complement proteins were screened in IgAN patients, and their correlations with laboratory or pathological parameters were analyzed. Thereafter, 7 complement components were validated by enzyme-linked immunosorbent assay (ELISA) in the urine samples of 45 IgAN patients. Results There were 786 differentially expressed proteins between IgAN and HC. KEGG analysis showed that differentially expressed urinary proteins in IgAN were enriched with complement. Of these, 67% of urinary complement protein abundance was associated with the estimated glomerular filtration rate. The urinary complement-related protein collectin12 (colec12), complement H factor (CFH), complement H factor-related protein 2 (CFHR2), and complement B factor (CFB) were positively correlated with serum creatinine; colec12, CFHR2, CFB, and C8g were positively correlated with glomerulosclerosis; CFH, CFHR2, C8g, and C9 were positively correlated with tubular atrophy/interstitial fibrosis. Conclusion Abnormally increased components of complement pathways significantly correlate with reduced renal function, proteinuria, and renal histological damage in IgAN. It could provide a potential biomarker panel for monitoring IgAN and provide clues for therapeutic choice targeting complement system of IgAN patients.